2016
DOI: 10.1002/mnfr.201500751
|View full text |Cite
|
Sign up to set email alerts
|

The dietary flavonol quercetin ameliorates angiotensin II‐induced redox signaling imbalance in a human umbilical vein endothelial cell model of endothelial dysfunction via ablation of p47phox expression

Abstract: Physiologically obtainable quercetin concentrations are capable of ameliorating angiotensin II-induced endothelial nitric oxide and superoxide imbalance via protein kinase C-independent restoration of p47(phox) gene and protein expression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 34 publications
1
11
0
Order By: Relevance
“…to inhibit overexpression and phosphorylation of p47phox in RAW249.7 cells and endothelial cells (Kim et al 2013;Jones et al 2016), respectively. Indeed, the effects of the combined treatment with SR and AGIQ might be related to oxidative stress, since both the treatment increased expression antioxidant gene, Catalase.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…to inhibit overexpression and phosphorylation of p47phox in RAW249.7 cells and endothelial cells (Kim et al 2013;Jones et al 2016), respectively. Indeed, the effects of the combined treatment with SR and AGIQ might be related to oxidative stress, since both the treatment increased expression antioxidant gene, Catalase.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism of combined effects of SR and AGIQ on chemoprevention toward early hepatocarcinogenesis might involve NOX-related pathways, since the combined treatment with SR and AGIQ reduced expression of p22phox in the liver foci. SR inhibits expression of NOX components RAC1 and NOX4 by modulating MR in a normal rat kidney cell line NRK-52E (Tsuji et al 2016), while isoquercitrin is also known to inhibit overexpression and phosphorylation of p47phox in RAW249.7 cells and endothelial cells (Kim et al 2013; Jones et al 2016), respectively. Indeed, the effects of the combined treatment with SR and AGIQ might be related to oxidative stress, since both the treatment increased expression antioxidant gene, Catalase .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…EA.hy296 cell line incubated with different concentrations of red wine polyphenol extract (100-600 µg/ml) for 18 h produced a significant increase in nitric oxide level (Leikert et al 2002). Ugusman et al (2014) showed that rutin administration at concentrations of 300 µM significantly increased the level of nitric oxide after being added to HUVEC cells for 24 h. Nitric oxide level was also significantly increased in a dose-dependent manner after incubating the HUVEC cell line for 8 h with quercetin (Jones et al 2016).…”
Section: Discussionmentioning
confidence: 98%
“…This hyperpolarization is carried out to VSMCs that inhibits extracellular Ca +2 influx and release from endoplasmic reticulum (Maaliki, Shaito, Pintus, El‐Yazbi, & Eid, 2019; Satoh & Nishida, 2014). Furthermore, quercetin decreases oxidative stress in heart, kidney, and endothelial cells by quenching the activity of NADPH oxidase and expression of the subunits p47phox, NOX1, and NOX4 (Jones et al, 2016; Oyagbemi et al, 2018). NADPH oxidase transfers electron from NADPH to molecular oxygen‐generating superoxide anion that inactivates NO and is involved in endothelial dysfunction (Brandes, 2010).…”
Section: Potential Mechanisms Of Antihypertensive Activity Of Berriesmentioning
confidence: 99%